Analisis Kinerja Badan Penanggulangan Bencana Daerah (BPBD) Kota Semarang - Irvan Indriyan; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Indonesia has very high potential of disaster. Semarang city is one of the cities in Indonesia, which has high potential of disaster. Badan Penanggulangan Bencana Daerah (BPBD) Semarang is government institution which is responsible to overcome or manage disaster that happen in Semarang City, but the achievement of the performance is still volatile. The purpose of the research to analyze the performance and the supporting and obstructing factor that influence the performance of Badan Penanggulangan Bencana Daerah (BPBD) Semarang. This type of research is descriptive qualitative. Techniques used in selecting informants with the snowball technique. Source of data in this research are primary data and secondary data. Data collection techniques are interviews, observation, documentation, and literature. In this research used triangulation technique for analyzing the data obtained. The performance of BPBD Semarang city has been able to say good but not optimal. Productivity in BPBD Semarang city has been good, with the efforts to increase productivity. But is still constrained by its dependence on another institution in disaster management. Responsiveness BPBD Semarang city is good at recognizing and accepting the aspirations of society. Accountability BPBD Semarang city has been good, with transparency and accountability that has been done. Factors supporting the performance of Badan Penanggulangan Bencana Daerah (BPBD) Semarang is a factor of a good team in the coordination and support among employees. Cultural organizations in BPBD Semarang city was already in accordance with the dimensions of performance, namely performance, teamwork, and loyalty work. Leadership in BPBD Semarang city was already implementing openness in decision-making and for good guidance and direction from the leadership to employees. Factors obstructing the performance of BPBD Semarang city is still not the reward for employee performance and still dependence on third parties in disaster management. Based on the research, The performance of BPBD Semarang City is very good but not optimum yet. There are some recommendation that the writer give to optimize the employee performance such as giving reward to the employee for certain achievement and doing innovation in managing disaster in order to not depending on another institution.